Precision and accuracy of transcutaneous CO2 monitoring in infants born at 32-36 weeks of pregnancy on respiratory support - Lubis, Syamsidah; Kaban, Risma Kerina; Dewi, Rismala; Putri, Ruth Angelia (Indonesian Pediatric Society, 2024)
Background Respiratory disorders in premature neonates often require respiratory support. Continous transcutaneous monitoring is an available non-invasive option to monitor CO2 pressure, substituting the need for blood gas analysis as the gold standard evaluation in practice. Most studies have been conducted on very and extremely preterm neonates, but rarely in late and moderately preterm neonates. Objective To determine the precision and accuracy of transcutaneous CO2 pressure measuring devices compared to arterial blood gas analysis in neonates of 32-36 weeks gestational age who received respiratory support. Methods This diagnostic, cross-sectional study was conducted on 35 late and moderately preterm neonates of 32–36 weeks gestation who received cardiopulmonary resuscitation (CPR) in the Neonatology Unit at Rumah Sakit Cipto Mangunkusumo, Jakarta. Subjects were monitored with a transcutaneous CO2 monitor and blood gas analysis (BGA). CO2 pressure measurements were made three times from the two devices. Data were analyzed using Spearman’s correlation and Bland-Altman tests to determine the precision and accuracy of transcutaneous monitoring by comparing its mean difference (MD) to BGA as the gold standard measurement. Results Spearman’s analysis revealed a significant positive correlation between BGA and transcutaneous CO2 monitoring (P<0.001). However, the Bland - Altman test revealed a level of agreement between measuring devices was -14.46 to 6.9, with mean difference of -3.78; indicating poor precision of the transcutaneous evaluation regardless its high accuracy compared to its gold standard. Conclusion The transcutaneous CO2 monitoring device has low precision, but a strong positive correlation to BGA; underlining its high accuracy in practice. Transcutaneous CO2 monitoring cannot replace BGA, the gold standard examination.